Performance of La1-xSrxCr1-yMnyO3-δ anode materials for intermediate temperature solid oxide fuel cell - 陈秀华 马文会 杨斌 戴永年 (Transactions of Nonferrous Metals Society of China, 2007)
La1-xSrxCr1-yMnyO3-δ（LSCM） anode materials were synthesized by glycine nitrate process（GNP）. Thermo-gravimetric analysis（TGA） and differential scanning calorimetric（DSC） methods were adopted to investigate the reaction process of LSCM anode materials. The oxides prepared were characterized via X-ray diffraction（XRD）, scanning electron microscope and energy dispersive spectroscopy（SEM-EDS）, direct current four-electrode and temperature process reduction（TPR） techniques. XRD patterns indicate that perovskite phase created after the precursor was sintered at 1 000℃ for 5 h, and single perovskite-type oxides formed after the precursor were sintered at 1 200 ~C for 5 h. The powders are micrometer size after sintering at 1 000 ℃ and 1 200℃, respectively. The conductivities of LSCM samples increase linearly with increasing the temperature from 250 ℃ to 850 ℃ in air and the maximum value is 32 S/cm for La1-xSrxCr1-yMnyO3-δ. But it is lower about two orders of magnitude in pure hydrogen or methane than that of the same sample in the air. TPR result indicates that LSCM offers excellently catalytic performance.